Initial Surface Absorption of Cement Combination Concretes Containing Portland Cement, Fly Ash, Silica Fume and Metakaolin - Folagbade, Samuel Olufemi (International Journal of Sustainable Construction Engineering and Technology, 2017)
In order to support the use of cement combination concrete in construction, this paper investigated the initial surface absorption of cement combination concrete using Portland cement and some binary and ternary cement concretes containing fly ash, silica fume and metakaolin as partial replacements for Portland cement at equal water/cement ratios and strengths. At equal water/cement ratio, the cement combination concretes have higher initial surface absorption values than Portland cement concrete at 28 days and the disparity reduced due to improved pozzolanic reactivity of the supplementary cements with increasing curing age. However, silica fume and metakaolin as binary and ternary cement components performed better than fly ash due to their higher fineness, improved particle packing and higher pozzolanic reactivity. At equal strengths, fly ash binary cement concretes have the lowest ISAT 10 values and they reduced with increasing content of fly ash. At total replacement levels more than 20%, all the ternary cement concretes have lower ISAT 10 values than Portland cement concrete and the values reduced with increasing total replacement level due to the beneficial effect of fly ash. Hence, high volume of fly ash would be required to improve the resistance of concrete against permeation.